Audit quality attributes - Chua, Saw Leng (2014)
This study aims to compare perceptions of the underlying components of audit quality by surveying auditors, clients and financial statement users and to determine any difference in results derived compared to Carcello’s study (an US study). Average means of 3 groups were computed based on the raw data gathered. Characteristics related to members of the audit team were generally perceived by the respondents to have more contribution to audit quality than characteristics related to the audit firm itself.